Clinical outcomes of interposition arthroplasty for surgical rigid hallux correction in a quaternary hospital in the metropolitan region of São Paulo - Gonzalez Corrêa, Fernando; ISDM, Castro; Fernandez Maringolo, Leonardo (Journal of the Foot & Ankle, 2026)
Introduction: This is a retrospective case series comprising ten patients diagnosed with rigid hallux grades III and IV, followed for a mean of two years. The sample was predominantly female (90%). Patients refractory to conservative treatment for at least six months were included. Individuals with diabetes mellitus, rheumatoid arthritis, or previous surgeries in the metatarsophalangeal joint were excluded. Methods: The surgical technique consisted of a dorsal approach, making a “U” shaped capsular flap with a distal base, partial resection of the base of the proximal phalanx and the head of the first metatarsal, followed by interposition and fixation of the capsular tissue with a non-absorbable suture. The postoperative protocol prioritized early mobilization and immediate loading with surgical footwear. Clinical outcomes were assessed using the visual analog scale (VAS) and the AOFAS. Results: The results demonstrate that capsular interposition arthroplasty is a safe and long-lasting alternative for the treatment of advanced rigid hallux in selected patients. Compared to studies that reported high rates of metatarsalgia and cock-up deformity, the present cohort had a low rate of complications and a longer time to eventual failure. Conclusion: The preservation of joint mobility distinguishes this technique from primary arthrodesis and is particularly relevant in physically active patients. The main limitations include the retrospective design, absence of a control group, and losses at follow-up. Still, the long follow-up period reinforces interposition arthroplasty as a viable alternative for postponing or avoiding definitive fusion.